Decomposiç\~ao estrutural e desigualdade do consumo de energia no Brasil por classe de renda - Amaro Olimpio Pereira Júnior; Rodrigo Maia; Mario Jorge Mendonça; Paulo Roberto Santos Casaca (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This paper aims to analyze the impact of an improvement in income distribution on energy consumption in Brazil, based on structural decomposition techniques. For this purpose, hybrid input-output matrices are constructed to associate the evolution of national accounts with the national energy matrix. Household consumption is decomposed into ten income classes. The results show that the improvement in income distribution are reflected in the increase in energy consumption, which was attenuated by the process of deindustrialization in the country. On the other hand, there were no energy efficiency gains in production processes. Such results are important for the construction of energy demand and greenhouse gas emissions scenarios to achieve the Brazilian targets compatible with sustainable development.
Keywords: C67; D57; C80; 330; structural decomposition; energy models; hybrid input-output matrix; income distribution; household budget survey